Mesophotic Coral Ecosystems: A Geoacoustically Derived Proxy for Habitat and Relative Diversity for the Leeward Shelf of Bonaire, Dutch Caribbean - Trembanis, Arthur C.; Forrest, Alexander L.; Keller, Bryan M.; Patterson, Mark R. (Frontiers in Marine Science, 2017)
Current trends demonstrate coral reef health in serious decline worldwide. Some of the most well preserved coral reefs in the Caribbean basin are located in the waters surrounding Bonaire, in the Dutch Caribbean. In many places on the leeward side on islands dominated by trade winds, the shallow reef systems extend into deeper water where they are known as Mesophotic Coral Ecosystems (MCE). Autonomous Underwater Vehicles (AUVs) were used to collect geoacoustic data of these leeward reefs at multiple sites as part of an ocean exploration project. AUV swath bathymetry and side-scan sonar data were analyzed for depth, acoustic backscatter intensity, seafloor slope and rugosity. These geomorphic metrics were then used as inputs to generate a composite synthetic index of bottom-type to delineate MCE features. A confusion matrix statistical analysis of the acoustic class map showed an overall accuracy of the acoustic classes at 66%, with accuracy of the hard coral class the highest at 83% and the sandy-bottom class the lowest at 55. The hard coral class was also the statistically most reliable, at over 80%, with the noise class coming in as the least reliable. This morphologic habitat index is a potentially useful new tool in quantifying the extent of MCE located in proximity to Marine Protected Areas (MPAs).